Penerapan Awig-Awig Terhadap Tamiu di Desa Adat Mengwi Kabupaten Badung - Putu Agustina Mega Antari; Anak Agung Sagung Laksmi Dewi; I Ketut Sukadana (Fakultas Hukum Universitas Warmadewa, 2024)
Currently, there are various population issues related to the various customary laws that are applied. Currently, topics related to population often arise, one of which is specifically related to the customary laws that apply in Bali. One of them is fundraising for immigrants. The collection is done every month by the Pakraman Village Security Guard. There is little obstruction or resistance in tamiu, as residents should be free to live wherever they want. This research has two specific objectives, namely to find out and investigate the Krama arrangements and obstacles to the adoption of Awig-Awig for Tamiu in Mengwi Traditional Village, Badung. area This type of research approach uses legal sociology because through this research the author can understand the problems that exist in the field. The data of this research is information obtained directly from informants, namely the Head of the Mengwi Customary Village, and respondents, namely the Tamiu community, in accordance with the Awig-Awig Regulation of the Mengwi Customary Village Pawos (Article) 26 while the rights of the Tamiu community are protected in the form of disaster management and actions. indigenous decisions, if there is a problem, get their rights to remain recognized by the local population.